The reliability and validity of the Turkish version of Fullerton Advanced Balance (FAB-T) scale - Iyigun, Gozde; Kirmizigil, Berkiye; Angin, Ender; Oksuz, Sevim; Can, Filiz; Eker, Levent; Rose, Debra J. (Elsevier Ireland Ltd, 2018)
Purpose: The aim of this study was to evaluate the reliability and validity of the Turkish version of the FAB(FAB-T) scale in the older Turkish adults. Methods: The reliability and validity of the scale was tested on 200 community-dwelling older adults. FAB-T scale was scored by different physiotherapists on different days to evaluate inter-rater and intrarater reliability. The Berg Balance Scale (BBS) was used for the evaluation of convergent validity, and the content validity of the FAB-T scale was investigated. Results: The FAB-T scale showed very high inter- and intra-rater reliability. For inter-rater agreement, on the individual test items and total score ICC values were 0.92 (95 %CI; 0.90-0.94) and 0.96 (95% CI; 0.95-0.97) respectively. The intra-rater agreement, on the individual test items and total score ICC values were 0.93 (95 %CI; 0.91- 0.95) and 0.96 (95% CI; 0.95- 0.97) respectively. There was a good agreement between the FAB-T and BBS scales. A high correlation was found between the BBS and FAB-T scales [rho = 0.70 (%95 CI; 0.62-0.76)] indicating good convergent validity. Considering the content validity of the FAB-T scale, no floor (floor score: 0%) or ceiling (ceiling score: 6.5%) effect was detected. Conclusion: : The FAB-T scale was successfully translated from the original English version (FAB) and demonstrated strong psychometric features. It was found that the FAB-T scale has very high inter-rater and intra-rater reliability. Considering the convergent validity, the scale has high correlation with the BBS. The FAB-T has no floor and ceiling effect.
Keywords: Reliability; Validity; Fullerton advanced balance scale; Turkish; Older adults